Professional competence as a by-product of gaming-as-a-hobby : A descriptive survey study - Törhönen, Juho (My University, 2024)
While the potential harmful effects of video games have been studied extensively, less attention has been given to their potential benefits. This is especially true for the potential benefits to career driving competences. While some research has been conducted on specific competences or contexts such as attention allocation and problem-solving, they are usually either only focused on those specific competences or specific game genres, such as shooter or simulation games. The purpose of this study is to broaden that view to a wider perspective of competence development as a by-product of playing video games as a hobby. Prior literature suggests that there are noticeable similarities between competences that companies’ desire and universities aim to develop, with the competences that can be developed by playing video games as a hobby. These attainable and desired competences were used to create a survey targeted at knowledge workers, to find out how they perceive that video games have affected the development of those competences, while also collecting some demographical data to find any meaningful correlations. The number of respondents was n = 55 and provided a dataset for analysis using descriptive survey research methodology. The study shows that players also tend to see a positive impact on their competences from video gaming as a hobby, although there is a wide variety across different competences and their subcategories. Altogether, respondents viewed the effect of playing video games as a hobby positively regarding competence development. Additionally, according to the results of the literature review and empirical data, the selection of game genre is directly connected to what competences can be developed, while other player demographical data such as age group and gaming platform seem to only influence how competence development as a side-product of playing video games is perceived by players.

Vaikka videopelien mahdollisia haitallisia vaikutuksia on tutkittu laajalti, niiden potentiaalisiin hyötyihin on kiinnitetty selvästi vähemmän huomiota. Tämä pätee erityisesti videopelien pelaamisen tarjoamiin hyötyihin työelämäkyvykkyyksien kehittymisessä. Vaikka joitakin tutkimuksia on tehty tiettyihin kyvykkyyksiin, kuten huomion kohdentamiseen ja ongelmanratkaisuun, liittyen, ne keskittyvät yleensä joko vain kyseessä oleviin kyvykkyyksiin tai tiettyihin peligenreihin, kuten räiskintä- tai simulaatiopeleihin. Tämän tutkimuksen tarkoituksena on avartaa näkemystä osaamisen kehittymisestä videopelien pelaamisen sivutuotteena. Aiemman kirjallisuuden mukaan yritysten ja yliopistojen haluamien ja videopelejä harrastuksena pelaamalla kehitettävien kyvykkyyksien välillä on yhtäläisyyksiä. Näitä kirjallisuuden perusteella saavutettavissa olevia ja haluttuja kyvykkyyksiä käytettiin tietotyöntekijöille suunnatun tutkimuskyselyn luomiseen. Sillä selvitettiin, miten he kokevat videopelien vaikuttaneen tietotyössä hyödyllisten kyvykkyyksien kehitykseen. Ohessa kerättiin myös joitain demografisia tietoja merkityksellisten korrelaatioiden löytämiseksi, esimerkiksi vaikuttaako pelaajan ikä tai peliaika viikossa pelaajan näkemykseen kykyjen kehityksestä. Vastaajien määrä oli n = 55, ja se tarjosi aineiston analysoitavaksi kuvailevalla kyselytutkimusmenetelmällä. Tutkimus osoittaa, että pelaajat näkevät positiivisen vaikutuksen kyvykkyyksien kehittymiseen videopelaamisesta harrastuksena, vaikka eri kyvykkyyksissä ja niiden kategorioissa onkin paljon vaihtelua. Kaiken kaikkiaan vastaajat suhtautuivat videopelien pelaamisen vaikutukseen kyvykkyyksien kehittämisen kannalta keskimäärin myönteisesti. Lisäksi kirjallisuuskatsauksen tulosten ja empiirisen aineiston mukaan peligenren valinta on suoraan yhteydessä siihen, mitä kyvykkyyksiä voidaan kehittää, kun taas muut pelaajien demografiset attribuutit, kuten ikäryhmä ja pelialusta, näyttävät vaikuttavan siihen vain yleisemmällä tasolla.
Keywords: video games, competence, competence development, videopelit, kyvykkyydet, kyvykkyyksien kehittäminen